Down-Bore Velocimetry of an Explosively Driven Light-Gas Gun. (2015) - Huneault, Justin; Loiseau, Jason; Hildebrand, Myles; Higgins, Andrew
Abstract: Hypervelocity launchers are used in a number science and engineering applications. The ability of the two-stage light-gas gun to launch relatively large and well characterized projectiles to hypervelocity has made it the launcher of choice for a wide range of hypervelocity impact research fields. However, practical concerns typically limit launcher operation to 8 km/s. This work will present the development of an explosively driven light-gas gun in which the linear implosion of a thin walled steel tube is used to dynamically compress helium gas, which subsequently expands to propel a projectile. Despite modest development efforts, the implosion-driven launcher has demonstrated the ability to launch a 0.36-g projectile to 10.4 km/s. This study will focus on a down-bore velocimetry experiment of an implosion-driven launcher using a photonic Doppler velocimetry system which was able to track the projectile velocity up to 7.8 km/s. The observed projectile acceleration is significantly higher than internal ballistic model predictions. It is proposed that mixing of ablated wall material with the light gas in the launcher driver is responsible for the anomalously high projectile acceleration.